Youth Custody: Exercising Our Rights and Responsibilities to Indigenous Youth - Wickham, Molly (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2010)
Colonization is a common experience amongst Indigenous youth; the effects of which have contributed to an over representation of Indigenous youth in correctional facilities in British Columbia (B.C). Placing youth in custody violates Indigenous values and child rearing practices and advances internalized oppression by focusing on the individual as the problem. In order to counter these effects, Indigenous youth in custody require education and engagement in the areas of colonization and decolonization. This paper discusses how the youth justice system in B.C fails Indigenous youth and how one group of young Indigenous people have acted upon their responsibility to support their incarcerated brothers and sisters.